Evidence-based recommendations for communicating the impacts of climate change on health. Issue 4 (25th May 2022) - Peters, Ellen; Boyd, Patrick; Cameron, Linda D; Contractor, Noshir; Diefenbach, Michael A; Fleszar-Pavlovic, Sara; Markowitz, Ezra; Salas, Renee N; Stephens, Keri K
Abstract: Climate change poses a multifaceted, complex, and existential threat to human health and well-being, but efforts to communicate these threats to the public lag behind what we know how to do in communication research. Effective communication about climate change's health risks can improve a wide variety of individual and population health-related outcomes by: (1) helping people better make the connection between climate change and health risks and (2) empowering them to act on that newfound knowledge and understanding. The aim of this manuscript is to highlight communication methods that have received empirical support for improving knowledge uptake and/or driving higher-quality decision making and healthier behaviors and to recommend how to apply them at the intersection of climate change and health. This expert consensus about effective communication methods can be used by healthcare professionals, decision makers, governments, the general public, and other stakeholders including sectors outside of health. In particular, we argue for the use of 11 theory-based, evidence-supported communication strategies and practices. These methods range from leveraging social networks to making careful choices about the use of language, narratives, emotions, visual images, and statistics. Message testing with appropriate groups is also key. When implemented properly, these approaches are likely to improve the outcomes of climate change and health communication efforts. Lay Summary: Climate change poses a tremendous and complex threat to human health and well-being. Efforts to communicate these threats to the public may not be as effective as desired and using evidence-based strategies could improve a wide variety of health-related outcomes for individuals and society while potentially reducing climate-related health disparities. In particular, effective communication can help people understand the crucial connection between climate change and health risks and empower them to act on that newfound knowledge and understanding. We recommend 11 communication methods that have been well tested in other domains and can be applied to the intersection of climate and health by healthcare professionals, decisionmakers, governments, the general public, and other stakeholders including those in sectors outside of health. These methods range from leveraging social networks to making careful choices about the use of language, narratives, emotions, visual images, and statistics. Message testing with appropriate groups is also key. When implemented properly, these approaches are likely to improve knowledge uptake and drive better decision making and healthier behaviors. Abstract : Evidence-based communication techniques can be used to empower people to act on newfound knowledge about the critical intersection of climate and health.